Current treatment of chronic hepatitis B: Clinical aspects and future directions - Zhu, Minmin; Wang, Hui; Lou, Tao; Xiong, Pian; Zhang, Jiebing; Li, Lele; Sun, Yuchao; Wu, Yingping (Frontiers in Microbiology, 2022)
Hepatitis B virus (HBV) infection is a public health threat worldwide, and there is no direct treatment yet available. In the event of infection, patients may present liver cirrhosis and cancer, which threaten the patients’ health globally, especially in the Asia-Pacific region and China. In 2019, Chinese hepatopathologists updated the 2015 Guidelines for the Prevention and Treatment of Chronic Hepatitis B as the clinical reference. The other versions formulated by the American Association for the Study of Liver Diseases (2018 AASLD guidelines) (AASLD, 2018), European Association for the Study of Liver (2017 EASL guidelines) (EASL, 2017), and Asian-Pacific Association for the Study of the Liver (2015 APASL guidelines) (APASL, 2015) also provide clinical guidance. However, there are still some issues that need to be addressed. In the present study, the following aspects will be introduced successively: 1) Who should be treated in the general population according to the guidelines; 2) Treatment of specific populations infected with HBV; 3) Controversial issues in clinical practice; 4) Perspective.